Examining the impact of EU cohesion policies aiming to reduce regional and social disparities with examples of policy impacts in Ireland - Williams, Brendan. Autor; Varghese, Johanna. Autor (IGiPZ PAN, 2018)
This research describes the evolution of the Irish spatial planning system and explores the impact of EU cohesion policies aiming to reduce regional and social disparities within the European Union with respect to recent developments in Ireland. The changing nature of the Irish planning system is seen as movement from a market or local development led approach towards a more strategic regional and national approach. This trend has in part been influenced by EU policies, directives and initiatives with evidence of both difficulties and successful delivery of some major projects. The discussion is complemented by evidence from two case studies in the transportation area and interviews with key participants in the policy processes. In conclusion the implications of such trends for future planning policy in Ireland and the EU are explored.
29 cm
Każdy numer posiada własny tytuł.
Keywords: Unia Europejska; Irlandia; planowanie przestrzenne; infrastruktura transportowa; regiony peryferyjne

Functional polarization of Poland’s North-Eastern small towns in the light of R. Camagni’s concept of territorial competitiveness - Korcelli-Olejniczak, Ewa. Autor; Piotrowski, Filip. Autor; Melnyk, Maryana. Autor (IGiPZ PAN, 2022)
Small towns’ functions are exposed to pressure stemming from globalization and metropolitan development. In North-East Poland, the study area, they are at the same time affected by the restructuring of rural economy. As in other peripheral regions in Europe, they are subject to de-population trends. The analysis of socioeconomic functions performed by small towns reveals functional polarization – a division line between local service centers and those towns additionally performing specialized functions. Whereas some towns succeed in sustaining, or attracting, often niche type industrial and service activities, others remain to rely upon the provision of private and public services for the surrounding rural places. By referring to R. Camagni’s conceptualization of territorial competitiveness, the role of selected territorial capital components – local entrepreneurship, social capital and local leadership is identified in the observed development of socio-economic functions of supra-local market range. The findings reveal the focusing, by the successful local firms upon the specificity of market offer, its linking with local tradition, skills, and natural resources. On the conceptual side, at a town level, they indicate the importance of mutual interlocking of individual endogenous factors in the development and the sustenance of competitive functions.
24 cm
Keywords: małe miasta; funkcje wyspecjalizowane; konkurencja terytorialna; region peryferyjny; Polska Północno-Wschodnia

Przegląd Geograficzny T. 52 z. 4 (1980) (IGiPZ PAN, 1980)
24 cm
Keywords: Kazimierz Dziewoński; teorie systemu osadniczego; regiony geograficzno-historyczne; geografia regionalna; modele bazy ekonomicznej; dojazdy wahadłowe; urbanizacja; geografia miast; regiony peryferyjne; demografia; przyrost naturalny; migracje; konurbacja katowicka; Lizbona

Europa XXI 15 (2006) - Komornicki, Tomasz. Red.; Czapiewski, Konrad. Red. (IGiPZ PAN, 2006)
234 s. ; 24 cm
Keywords: Gospodarka regionalna -- Kraje Unii Europejskiej -- 1990- [KABA]; Kraje Unii Europejskiej -- sytuacja gospodarcza -- zróżnicowanie regionalne -- 1990- [KABA]; regiony peryferyjne; krajobrazy kulturowe; rozwój regionalny; obszary wiejskie; transport; sieci kolejowe; wspłólpraca transgraniczna; obszary sukcesu gospodarczego; peryferyjność; użytkowanie ziemi; demografia; potencjał demograficzny; starzenie się ludności; Niemcy; Czechy; Słowacja; Litwa; Polska; Rumunia; Słowenia; Bułgaria

Europa XXI 12 (2005) - Komornicki, Tomasz. Red.; Czapiewski, Konrad. Red. (IGiPZ PAN, 2005)
225 s. ; 24 cm
Keywords: Zagospodarowanie terenu -- Europa Wschodnia --1900- [KABA]; Geografia człowieka -- Europa wschodnia -- 1900- [KABA]; rozwój zrównoważony; konflikty ekologiczne; regiony peryferyjne; konflikty przestrzenne; wykluczenie społeczne; małe miasta; rewitalizacja miast; jakość życia; ludność; dojazdy do pracy; bezrobocie; motoryzacja; Polska; Węgry; Budapeszt; Bratysława; Niemcy; Słowacja; Bułgaria; Ukraina; Rosja